'We did it ourselves': The Deaf Social Movement and the Quest for the Legal Recognition of the Libras Sign Language in Brazil - Brito, F; Prieto, Ros (Disability Studies Quarterly, 2018)
This paper presents the results from a qualitative study on the history of the Deaf social movement in Brazil and the collective actions of its members to achieve legal recognition of Libras - the Brazilian Sign Language. The study was undertaken between 2009 and 2013 in several Brazilian capitals. We interviewed Deaf and hearing activists, Sign language specialists, Deaf education researchers, and members of the government. We also analysed written and audio-visual documents from personal collections and public and private institutions. These discoveries made it possible to trace the transformation in the Deaf community from its emergence in the context of the disabled social movements of the 1980s to the far more public demonstrations in the 1990s. The study also looks at the progressive empowerment of the movement's members, and their collectively defined ideologies, that were designed to promote and justify their political agenda. The paper also attempts to clarify the movement's role in the approval of the Libras Federal Law 10.436 of April 2002, regulated by decree 5.626 in December 2005, and discusses its importance in guaranteeing government bilingual educational policies for Deaf students.